Nanotechnology standards - Murashov, Vladimir (Nanostructure Science and Technology., 2011)
Written by a team of experts, Nanotechnology Standards provides the first comprehensive, state-of-the-art reviews of nanotechnology standards development, both in the field of standards development and in specific areas of nanotechnology. It also describes global standards-developing processes for nanotechnology, which can be extended to other emerging technologies. For topics related to nanotechnology, the reviews summarize active areas of standards development, supporting knowledge and future directions in easy-to-understand language aimed at a broad technical audience. Therefore, this unique book is an excellent resource for up-to-date information on the growing base of knowledge supporting the introduction of nanotechnology standards and applications into the market. Praise for this volume: ?This book provides a valuable and detailed overview of current activities and issues relevant to the area as well as a useful summary of the short history of standardization for nanotechnologies and the somewhat longer history of standardization in general. I have no hesitation in recommending this book to anyone with an interest in nanotechnologies whether it be from a technical or societal perspective.? -- Dr. Peter Hatto, Chairman ISO TC 229 and CEN TC 352 nanotechnologies technical committees, Director of Research, Ionbond Limited, Co Durham, UK.